PERSPECTIVE OF JOSEPH M. JURAN'S EDUCATIONAL QUALITY DEVELOPMENT MODEL AND IMPLEMENTATION IN EDUCATIONAL PROSPECTS - Andriani, Ulfia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The impact of the globalization era demands quality human resources, namely human resources who are able to face various challenges, changes and also global competition. Quality human resources are created from quality education, so that improving and developing the quality of education is a top priority in managing educational institutions and is very important to do immediately. One quality development model that can be applied is Joseph's quality development model. M. Juran. Juran's quality development concept is actually a quality concept in the business world, which is oriented towards profit/material gain. However, this concept can be adopted/applied to educational institutions that are oriented towards the quality of educational services. Juran mentions the term quality as "quality is fitness for use", namely quality is conformity with customer needs. In the world of education, there are two terms for customers, namely internal customers (school principals, teachers, employees) and external customers (students, parents, government, job market, society). Furthermore, Juran also offers three stages in the process of achieving quality, which is more popularly known as the Juran trilogy, including: 1. quality planning, 2. quality control and 3. quality improvement